2022
DOI: 10.3389/fcell.2022.832887
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Injury in Diabetic Kidney Disease: A Focus on Mitochondrial Dysfunction

Abstract: Podocytes are a crucial cellular component in maintaining the glomerular filtration barrier, and their injury is the major determinant in the development of albuminuria and diabetic kidney disease (DKD). Podocytes are rich in mitochondria and heavily dependent on them for energy to maintain normal functions. Emerging evidence suggests that mitochondrial dysfunction is a key driver in the pathogenesis of podocyte injury in DKD. Impairment of mitochondrial function results in an energy crisis, oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 157 publications
0
29
0
Order By: Relevance
“…20 Emerging data from epidemiologic analyses, experimental studies, and clinical trials indicate DKD as a metabolic disorder, and the metabolic reprogramming of podocytes contributes to the pathogenesis of DKD. 21,22 Thus, targeting the metabolic pathways of podocytes is a promising therapeutic approach for DKD. In the current study, we revealed that LRH-1 positively modulated the Gln metabolism in podocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Emerging data from epidemiologic analyses, experimental studies, and clinical trials indicate DKD as a metabolic disorder, and the metabolic reprogramming of podocytes contributes to the pathogenesis of DKD. 21,22 Thus, targeting the metabolic pathways of podocytes is a promising therapeutic approach for DKD. In the current study, we revealed that LRH-1 positively modulated the Gln metabolism in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…DKD has become a significant cause of chronic kidney disease (CKD) and end‐stage renal disease (ESRD) 20 . Emerging data from epidemiologic analyses, experimental studies, and clinical trials indicate DKD as a metabolic disorder, and the metabolic reprogramming of podocytes contributes to the pathogenesis of DKD 21,22 . Thus, targeting the metabolic pathways of podocytes is a promising therapeutic approach for DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes are rich in mitochondria and rely on them for energy to maintain normal functions. Mitochondrial biogenesis, mitophagy, mitochondrial dynamics, mitochondrial oxidative phosphorylation, and oxidative stress, dysfunctions of all of the above processes are associated with podocyte damage in DKD ( Liu et al, 2022 ). Evidence showed that mitochondrial dysfunction contributes to the development and progression of fibrosis, including renal fibrosis ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DKD is a microvascular complication of DM that develops from micro-proteinuria to massive proteinuria, ultimately leading to end-stage renal disease (18). Importantly, metabolic and hemodynamic changes in DM cause ultrastructural changes in the glomerular filtration barrier, including podocyte foot process fusion and separation, GBM thickening, reduction of endothelial cell glycocalyx, accumulation of mesangial extracellular matrix, and glomerular sclerosis, all of which are directly related to the increase in proteinuria (20).…”
Section: Pathological Process Of Dkdmentioning
confidence: 99%